Coyote Steals the Blanket : An Ute Tale - Stevens, Janet (New York : Holiday House, 1993)
Recounts the story of the thieving Coyote, the beautiful blanket that he steals, and the Hummingbird, who tries to save Coyote from the wrath of the spirit of the great desert.
Keywords: Coyote (Legendary character); Ute Indians -- Legends; Indians of North America -- Legends